2018
DOI: 10.1136/annrheumdis-2018-213093
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ST3AGL4, MFHAS1, CSNK2A2 and CD226 as loci associated with systemic lupus erythematosus (SLE) and evaluation of SLE genetics in drug repositioning

Abstract: This study identified three novel loci associated with SLE and demonstrated the role of SLE GWAS findings in drug repositioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…These observations suggest a potentially distinct role for CD226 in controlling CD4 + T cell lineages, especially in Tregs. Despite evidence of the genetic associations of CD226 with autoimmune diseases and dysfunctional Tregs (7,44,45), as well as studies noting that CD226 + TIGIT − Tregs are associated with reduced suppressive capacity (46), the exact molecular mechanism and function role of CD226 in Tregs is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest a potentially distinct role for CD226 in controlling CD4 + T cell lineages, especially in Tregs. Despite evidence of the genetic associations of CD226 with autoimmune diseases and dysfunctional Tregs (7,44,45), as well as studies noting that CD226 + TIGIT − Tregs are associated with reduced suppressive capacity (46), the exact molecular mechanism and function role of CD226 in Tregs is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Further replication effort by Molineros et al confirmed five novel susceptibility loci ( MYNN , ATG16L2 , CCL22 , ANKS1A, and RNASEH2C ) in the Hong Kong cohort (Molineros et al, ). Our most recent work further identified ST3AGL4 , MFHAS1 , CSNK2A2, and CD226 to be associated with the disease (Wang et al, ).…”
Section: Replication Studies Of Gwas Findingsmentioning
confidence: 85%
“…This process highlights the significance of genetic studies in opening a window to understanding the functions of genes, although it may take years of functional characterizations. Our recent study showed enriched interaction between SLE susceptibility genes and targets for available SLE drugs, and demonstrated a potential role of genetic studies in drug repurposing (Wang et al, ).…”
Section: Functional Characterizations Of the Associated Genesmentioning
confidence: 87%
See 1 more Smart Citation
“…The GWAS datasets used in the discovery stage are from published studies (Bentham et al, 2015;Morris et al, 2016;Sun et al, 2016), with European cohorts comprising 4,943 SLE cases and 8,483 controls (EUR), and Asian cohorts including 2,485 cases and 3,947 controls (AS). The samples included in the replication stage in this study partially overlapped with those used in our previous studies (Yang et al, 2009(Yang et al, , 2011(Yang et al, , 2013Wanling et al, 2010;Li et al, 2012;Zhang et al, 2015aZhang et al, ,b,c, 2016Wang et al, 2018), which were collected from Hong Kong (1,255 SLE cases and 951 healthy controls, HK_rep) and Anhui Province, China (1,014 cases and 4,122 controls, AH_rep), respectively. Briefly, SLE cases in the Hong Kong cohort were recruited from five public hospitals in Hong Kong, namely Queen Mary Hospital, Tuen Mun Hospital, Queen Elizabeth Hospital, Princess Margaret Hospital, and Pamela Youde Nethersole Eastern Hospital.…”
Section: Subjectsmentioning
confidence: 99%